Wide‐Gap Perovskites for Indoor Photovoltaics - Gregory Burwell (Solar RRL, 2024)
Organic–inorganic halide perovskite semiconductors have revolutionized next-generation photovoltaics (PV) due to several characteristics such as solution-processability, gap tunability, and excellent charge generation and transport properties. This has made them very adaptable for various applications in light harvesting and photodetection. One such rapidly growing application is indoor photovoltaics (IPV) which have the potential to power standalone Internet of Things devices. IPV requires wider optimal bandgaps than solar cells (1.8 vs 1.3 eV) due to the differences between the spectra of artificial lights versus solar radiation. For IPV applications, the active layer wide-gap perovskite must be developed systemically considering all other components of the device, such as interlayers, electrodes, and scaling. This perspective provides an overview of the potential and challenges facing perovskite-based IPV from a theoretical, material, and experimental perspective. Furthermore, accurate characterization of perovskite IPVs under simulated indoor conditions is discussed and candidate perovskite PV (PPV) systems are presented to provide insight into IPV development. These include IPV-optimized formamidinium cesium-based perovskite, wide-gap p-i-n devices, and 2D perovskite devices, tested under spectrophotometrically calibrated LED illumination at various indoor-relevant illuminances and benchmarked against thermodynamic predictions. Finally, strategies required to create stable, optimized PPV devices for indoor applications are discussed.